The History of the Generational Evolution of the Labor Market: Indicators and Results (Based on the Materials of the Population Censuses in the Volgograd Region in 1979–2002) - Tatiana Ivanova (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The relevance and purpose of this study are determined by the importance of the labor market in regional development. The choice of an object is determined by the formation of an able-bodied population in different social conditions over a relatively short historical period of time and the need for assessment for subsequent forecasting of the changes that have occurred due to this. Materials and methods. The open materials of the All-Union (1979) and All-Russian (1989 and 2002) population censuses were used. Historical-evolutionary, historical-comparative, and statistical approaches, as well as the method of groupings based on the theory of generations, are applied. Results. For generations silent, baby boomers, X, Y (millennials), and Z, such characteristics as the share in the population, the ratio by sex, place of residence, features of sources of livelihood, types of activities, groups of occupations, and others were revealed. Their differences in the conditions of centralized, transitional, market-based public relation and commonality due to the general biological and digital conditions of formation, as well as the influence of these factors on the nature and depth of processing of the recorded indicators, are shown. Conclusions. The increasing propensity of younger generations to perform skilled labor functions, low willingness to engage in unskilled labor, and interest in diversifying activities. This implies the need for further restructuring of the labor relations system and methods of forecasting the appropriate directions of its transformation. Funding. The article was prepared with the financial support of the Russian Science Foundation and the Committee for Economic Policy and Development of the Volgograd Region, grant No. 24-28-20066, https://rscf.ru/project/24-28-20066/